Effects of Referral Bias on Estimates of Anal Intraepithelial Neoplasia Progression and Regression Rates in a 3-State Markov Model. Issue 35 (September 2015) - Mathews, William Christopher; Cachay, Edward Rafael; Agmas, Wollelaw; Jackson, Christopher; Akhilanand, Chaurasia.
<x xml:space="preserve">Abstract</x> Abstract The study aim is to compare anal intraepithelial neoplasia (AIN) progression and regression rates in a cytology inception cohort to estimates based on the subcohort referred for ≥1 high-resolution anoscopies (HRAs). A cytology-based retrospective cohort was assembled including the anal cytology histories and invasive anal cancer (IAC) outcomes of all HIV-infected adults under care between 2001 and 2012. A 3-state Markov model (<HSIL↔HSIL→IAC) was estimated separately for all patients and for the subcohort undergoing ≥ 1 HRAs with biopsy. Cytology was adjusted for misclassification. State transition rates (per person-year) and covariate hazard ratios were estimated using the R package msm. Of 2804 eligible patients in the inception cohort, 629 (22%) were in the HRA subcohort and 2175 (78%) in the non-HRA subcohort. Patients in the HRA subcohort were more likely to have baseline CD4<350, viral load >400, and to have HSIL at baseline and thereafter. They also had more anal cytology examinations (median 6 vs 3) and longer follow-up (median 5.5 vs 3.6 years). State transition rates were overestimated in the HRA subcohort relative to inception cohort, but the degree of discordance varied by transition: for <HSIL to HSIL (0.44 vs 0.04); for HSIL to <HSIL (0.56 vs 0.17); and for HSIL to IAC (0.014 vs 0.011). Beneficial covariate effects on the <HSIL to HSIL transition were concordant (P < 0.05) for time-updated HIV viral load, CD4 count, and antiretroviral therapy. The observed effects of HRA-triage bias may be relevant to estimates of AIN state transitions from other cohorts subject to referral bias.